Qing encounters: artistic exchanges between China and the West - Chu, Petra ten-Doesschate; Ding, Ning; Chu, Lidy Jane (Getty Research Institute, 2015)
"Qing Encounters: Artistic Exchanges between China and the West examines how the encounters between China and Europe in the eighteenth and early nineteenth centuries transformed the arts on both sides of the East-West divide. These essays reveal how trading and copying images, artifacts, and natural specimens inflected both cultures' visions of novelty and pleasure, battle and power, and ways of seeing and representing. Artists and craftspeople borrowed and adapted forms, techniques, and modes of representation, producing deliberate, meaningful, and complex hybrid creations. By considering this reciprocity from both Eastern and Western perspectives, Qing Encounters offers a new and nuanced understanding of this critical period"--Page 4 of cover
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte 1644-1912; Kulturkontakt; Kunst; Qingdynastie; Europa; China